2013
DOI: 10.1111/j.1464-410x.2012.11608.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation of renal tumours with clinical, radiographical and pathological results

Abstract: Objectives To evaluate our experience with radiofrequency ablation (RFA) for renal masses and to report on clinical, radiological and post-RFA biopsy results. Patients and methods The study collected clinical, radiological and pathological data from 150 consecutive patients who were treated with RFA of a renal mass between 2002 and 2008 at a tertiary referral centre. Post-ablation biopsies were performed in patients with non-involuting lesions or suspicion of recurrence on imaging. Comparisons were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The median (IQR) R.E.N.A.L. nephrometry score at time of surgery was 7 (5)(6)(7)(8)(9), while the median (IQR) time from ablation to surgery was 26.5 (16. .3) months.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The median (IQR) R.E.N.A.L. nephrometry score at time of surgery was 7 (5)(6)(7)(8)(9), while the median (IQR) time from ablation to surgery was 26.5 (16. .3) months.…”
Section: Resultsmentioning
confidence: 99%
“…Surgery was performed in two patients because of tumour progression with renal vein or inferior vena cava thrombus, in three patients because of failure of the tumour to shrink (with a positive preoperative biopsy) and in nine patients because of enhancement with contrast or tumour enlargement. Seven patients had percutaneous biopsy confirming recurrent disease, some of whom have been previously reported as part of our RFA experience [8]. Patients underwent surgery at the median (IQR) time of 26.5 (16.3-39.3) months after the ablation was performed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Karam et al [31] recently reported their experience of post-RFA radiographic features, and suggested that the absence of enhancement in tumors does not guarantee a successful ablation. Weight et al [32] also suggested radiologic findings were not reliable and recommended follow-up biopsy post RFA.…”
Section: Discussionmentioning
confidence: 99%